Determining factors in customer decision-making in choosing mortgage loans - Arum, Delfia Baby Sekar; Susana, Erni; Yuniriyanti, Eny; Dwipasari, Lita (Jurnal Penelitian, 2023)
This study aims to analyze the factors that influence customers' decisions regarding mortgage loans (Kredit Perumahan Rakyat or KPR), both individually and collectively. Using a sample of 90 participants selected through random sampling, data collection was carried out through a structured questionnaire. This study uses multiple linear regression analysis to determine the influence of various factors. The findings found that price level, service quality and procedural efficiency have a significant influence on customers' decisions in choosing mortgage loans. This highlights the important role these factors play in the customer decision-making process. In contrast, this study found that promotional activities did not have a significant influence on customer decisions, indicating a potential need for KPR providers to reassess their promotional strategies. Understanding these insights can assist KPR providers in tailoring their offerings to better align with customer preferences and needs, thereby strengthening their competitive advantage in the market landscape.